2020
DOI: 10.3389/fpsyg.2020.552416
|View full text |Cite
|
Sign up to set email alerts
|

Play Mode Effect of Exergames on Subthreshold Depression Older Adults: A Randomized Pilot Trial

Abstract: Background: Subthreshold depression is a common mental disorder in late life. Increasing studies have supported the positive effects of exergames to subthreshold depression. The current study aims to investigate how play mode potentially affects exergames' effects on subthreshold depression among older adults. Method: A between-group experiment was carried out to compare the effect of exergames with different play modes. Fifty-two Singaporean older adults with subthreshold depression were randomly assigned int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…However, a growing body of research has confirmed that exergames have an effect on reducing depression symptoms and have extended the posi-tive effects of exergames to subliminal depression. [14][15][16][17][18] In addition, it is well established that physical activity triggers the release of certain body chemicals (such as b-endorphins or dopamine), resulting in improved mood and a sense of wellbeing, 18 with implications for the quality of life. 4 Given the emerging phenomenon of an aging society around the world, special attention is needed not only for physical wellbeing but also for the psychological wellbeing of older adults in general, 16 which goes beyond interventions for different disorders and illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…However, a growing body of research has confirmed that exergames have an effect on reducing depression symptoms and have extended the posi-tive effects of exergames to subliminal depression. [14][15][16][17][18] In addition, it is well established that physical activity triggers the release of certain body chemicals (such as b-endorphins or dopamine), resulting in improved mood and a sense of wellbeing, 18 with implications for the quality of life. 4 Given the emerging phenomenon of an aging society around the world, special attention is needed not only for physical wellbeing but also for the psychological wellbeing of older adults in general, 16 which goes beyond interventions for different disorders and illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…A recent pilot study on play mode effects of exergaming on depression in older adults (Li et al. 2020 ) found that team-play could potentially reduce the experience of loneliness. Competition-based games have been shown to reduce intrinsic motivation (Song et al.…”
Section: Introductionmentioning
confidence: 99%
“…Like many other social exergames, the game in this study relied on adversarial game mechanics instead of centering the game around social collaboration. A recent pilot study on play mode effects of exergaming on depression in older adults (Li et al 2020) found that team-play could potentially reduce the experience of loneliness. Competition-based games have been shown to reduce intrinsic motivation (Song et al 2013) and lead to increased stress (Goršič et al 2017) and aggression (Pereira et al 2019).…”
Section: Introductionmentioning
confidence: 99%